Implementation of Meta Data Storage using Fragmentation method for more security in the cloud - Kiran Kumar, V; Hari Prasad, E (International Journal of Computer Sciences and Engineering, 2019)
Cloud Computing has wide range of opportunities for research and industry purpose. There are many issues to consider in cloud. The one of the main issue in cloud is Security. Protecting more secured data in cloud is a big task. To achieve more security for a sensitive data, a model is proposed .In this paper, providing more security for sensitive data is achieved by fragmenting the data and allocating the preferences to the data and only high secured data is encrypted and stored. The detailed implementation of the work is discussed clearly in the paper.